Back Cover: Tailored Synthesis of 162‐Residue S‐Monoglycosylated GM2‐Activator Protein (GM2AP) Analogues that Allows Facile Access to a Protein Library (ChemBioChem 20/2016). (30th September 2016) - Nakamura, Takahiro; Sato, Kohei; Naruse, Naoto; Kitakaze, Keisuke; Inokuma, Tsubasa; Hirokawa, Takatsugu; Shigenaga, Akira; Itoh, Kohji; Otaka, Akira
Abstract : The back cover picture shows a tailored synthesis of 162‐residue S‐monoglycosylated GM2‐activator protein (GM2AP) analogues. N ‐Sulfanylethylanilide (SEAlide), as a crypto‐thioester, and prolyl thioester peptides were successfully used in kinetically controlled ligation protocols. Tailored synthesis featuring the use of such kinetically controlled ligations allows facile access to a protein library of GM2AP analogues. More information can be found in the full paper by A. Otaka et al. onpage 1986 in Issue 20, 2016 (DOI:10.1002/cbic.201600400 ).